THAI SIGN LANGUAGE TO ENGLISH TRANSLATION USING VARIABLE HIDDEN NEURON ANN - A CASE STUDY - M N, Sowjanya; S N, Thimmaraju (International Journal of Research -GRANTHAALAYAH, 2021)
Sign language translation has been a major challenge in all walks of life. The current society has been more accepting of the specially abled and the government has been actively making policy changes to accommodate and assimilate the specially abled into the society. Every country has made a conscious effort to develop its own syllable set in its native language even though globally used language is American Sign Language (ASL). In this paper a method proposed by the authors for ASL is applied on Thai Sign Language and the working of the ANN model is explored.